2019
DOI: 10.1007/s40096-019-0290-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Joule heating on the flow over an exponentially stretching sheet with convective thermal condition

Abstract: This article analyzes the Joule heating effect on the viscous fluid flow over a porous sheet stretching exponentially by employing convective boundary condition. The numerical solutions to the governing equations are obtained using a local similarity and non-similarity approach together with a successive linearization procedure and a Chebyshev collocation method. The influence of the slip parameter, suction/injection parameter, magnetic parameter, Joule heating parameter and Biot number on the velocity, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The researchers obtained results from their examination that MHD becomes the root for inclusion in the thermal transfer of fluid in addition to the melting effect causes a decrease in the flow temperature. Srinivasacharya and Jagadeeshwar 22 computed the numerical analysis for MHD and Joule heating effects on an exponentially stretching surface under convective thermal conditions. They implemented the Chebeshev collocation method to attain the desired results.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers obtained results from their examination that MHD becomes the root for inclusion in the thermal transfer of fluid in addition to the melting effect causes a decrease in the flow temperature. Srinivasacharya and Jagadeeshwar 22 computed the numerical analysis for MHD and Joule heating effects on an exponentially stretching surface under convective thermal conditions. They implemented the Chebeshev collocation method to attain the desired results.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a steady two‐dimensional boundary layer flow of micropolar fluid over an exponentially shrinking sheet is analysed. In real applications, this flow problem may occur in the process of aerodynamic extrusion of plastic sheets, design of chemical processing equipment and field coating for welded pipes ends 41,42 . The flow problem is represented by the Cartesian plane such that the x axis is parallel to the sheet, and the y axis is normal to it, as illustrated in Figure 1.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Samuel (7) investigated the impact of hydromagnetic on Ohmic heating and viscous fluid on a porous sheet. Jagadeeshwar and Srinivasacharya (8) have numerically examined the heat transit of the Joule heating with convective boundary conditions on MHD fluid flow and they observed that the lower in Nusselt number as well as the higher in Biot number. The impact of Ohmic heating under the consideration of hydrodynamic flow through a stretching plate was deliberated by Gholinia et al (9) .…”
Section: Introductionmentioning
confidence: 99%